2013
DOI: 10.1177/0891988713476368
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Anxiety Symptoms in Parkinson Disease

Abstract: Anxiety may be present as an isolated symptom, with specific demographic and clinical markers, and not only as a feature of depression in PD population. This highlighted the importance of identifying anxiety symptoms when treating patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 37 publications
2
41
2
1
Order By: Relevance
“…Clinically significant depression may be present in 2.7% to 89% of PD patients (30) and a population-based study found an incidence rate among PD patients of nearly 26 cases per 1000 person-years, twice the incidence rate in the non-PD population (35). Anxiety risk in PD has been studied less extensively than depression, although many studies support a prevalence of 25–35% (31, 37, 43, 4951), with some reporting a frequency as high as 50–70% (32, 52). Risk of depression and anxiety in PD may be affected by sex (3234, 37), age at onset (32, 53), and disease duration (35, 49, 54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically significant depression may be present in 2.7% to 89% of PD patients (30) and a population-based study found an incidence rate among PD patients of nearly 26 cases per 1000 person-years, twice the incidence rate in the non-PD population (35). Anxiety risk in PD has been studied less extensively than depression, although many studies support a prevalence of 25–35% (31, 37, 43, 4951), with some reporting a frequency as high as 50–70% (32, 52). Risk of depression and anxiety in PD may be affected by sex (3234, 37), age at onset (32, 53), and disease duration (35, 49, 54).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of IPD, female sex is sometimes reported as a risk factor for anxiety (32, 37, 43) and depression (33, 34, 36); in addition, among those with early, drug-naïve Parkinson disease, women may demonstrate higher rates of anxiety than men (59). It is of interest, then, that in our post-hoc analysis separating GBA-PD and IPD by sex, we found that men with GBA-PD had a greater burden of trait-anxiety and of depression than men with IPD, but that there was no difference between women with GBA-PD and women with IPD.…”
Section: Discussionmentioning
confidence: 99%
“…A younger age of PD motor symptom onset is related to an increased risk of anxiety . Duration of PD diagnosis is positively correlated with anxiety in a number of studies . In contrast, Leentjens et al reported that longer disease duration is related to a reduction in anxiety disorders.…”
Section: Factors Associated With Anxiety In Pdmentioning
confidence: 99%
“…When restricted to individuals with clinically significant current anxiety disorders according to standardized criteria such as those of the Diagnostic and Statistical Manual of Mental Disorders (DSM) or the International Classification of Diseases (ICD), or to individuals exceeding cutoff score thresholds on anxiety rating scales, the reported current prevalence rates in PD vary between 12.8% and 43.0% . Lifetime prevalence estimates are not included in the current review because of concerns about possible recall bias .…”
Section: Variable and High Prevalence Of Current Anxiety In Pdmentioning
confidence: 99%
See 1 more Smart Citation